Epidural Analgesia With or Without Oxytocin, but Not Oxytocin Alone, Administered During Birth Disturbs Infant Pre-feeding and Sucking Behaviors and Maternal Oxytocin Levels in Connection With a Breastfeed Two Days Later - Takahashi, Yuki; Uvnäs-Moberg, Kerstin; Nissen, Eva; Lidfors, Lena; Ransjö-Arvidson, Anna-Berit; Jonas, Wibke (Frontiers in Neuroscience, 2021)
Aims To study consequences of medical interventions in connection with birth on infant pre-feeding and feeding behaviors and on maternal oxytocin levels in connection with a breastfeed two days later. Methods Mothers and their full-term newborns (n=41) were videotaped during a breastfeed two days after birth. Duration and quality of rooting (Infant Breastfeeding Assessment Tool (IBFAT)) were assessed. Maternal blood samples were collected and oxytocin levels were analyzed and mean oxytocin level and variance were calculated. Data on medical interventions during birth, number of breastfeeds and infant weight loss since birth were recorded. Data were analyzed using logistic regression models. Results The duration of infant rooting was significantly shorter when the mother had received epidural analgesia. The shorter the duration of infant rooting, the more often infants had breastfed and the greater was the infant weight loss since birth. Mothers with epidural analgesia with oxytocin had the lowest oxytocin mean levels in connection with a breastfeed. Oxytocin variance correlated positively with quality of rooting and correlated negatively with infant weight loss. In the control group alone, we found similar patterns of associations with oxytocin levels. Conclusion Epidural analgesia and epidural analgesia with oxytocin infusion in connection with birth negatively influenced infant rooting behavior and maternal mean oxytocin levels respectively. Oxytocin infusion alone was without effect. The data also suggest that infants who suckle well stimulate oxytocin release more efficiently, as expressed by a high oxytocin variance, leading to a better stimulation of milk production and consequently to a reduced infant weight loss two days after birth.